2004
DOI: 10.1016/s0002-9440(10)63380-9
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Lung Dendritic Cell Activation in CCR2 Knockout Mice

Abstract: Dendritic cell (DC) recruitment is a hallmark event in antigen (Ag)-challenged lungs. We previously reported models for analyzing DC migration and activation in the lung after Th1-or Th2-eliciting pathogen Ag-bead challenge. To determine the role of chemokines in DC mobilization, we applied this analysis to CCR1, CCR2, CCR5, and CCR6 chemokine receptor knockout mice. Both Mycobacteria bovis protein Ags and helminthic, Schistosoma mansoni egg Ags elicited multiple chemokines, including CCR1, CCR2, CCR5, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…The delayed recruitment of CD4 ϩ T cells to the lungs is consistent with impaired trafficking of CD4 ϩ and CD8 ϩ T cells to the site of inflammation in corona virus-infected CCR2Ϫ/Ϫ mice [20]. Immature DC from CCR2Ϫ/Ϫ mice exhibit defective maturation with significantly decreased MHC Class II and CD40 expression [44]. This may potentially result in impaired activation of CD4 ϩ T cells in CCR2Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 59%
“…The delayed recruitment of CD4 ϩ T cells to the lungs is consistent with impaired trafficking of CD4 ϩ and CD8 ϩ T cells to the site of inflammation in corona virus-infected CCR2Ϫ/Ϫ mice [20]. Immature DC from CCR2Ϫ/Ϫ mice exhibit defective maturation with significantly decreased MHC Class II and CD40 expression [44]. This may potentially result in impaired activation of CD4 ϩ T cells in CCR2Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 59%
“…Although recruitment was interpreted to be the major mechanism for changes in cell number in that study, a separate analysis of lung inflammation in response to Ag-coated beads identified an additional defect in maturation (i.e., up-regulation of MHC class II and CD40) in CD11c ϩ cells in CCR2 Ϫ/Ϫ mice (35). The differences in the methods used to identify DC precludes direct comparison of those results with the current data.…”
Section: Studies a Population Of Cd11cmentioning
confidence: 75%
“…iDC bind E-and P-selectins under shear stress (15), making this adhesive system a plausible requirement for their recruitment. The second class of potential recruitment molecules were the chemokine receptors CCR2 and CCR6, which have recently been implicated in DC recruitment to the lung (19,34,35), tonsils (36,37), and injured skin (36 -38). Our results demonstrate that, in response to a single Ag challenge, the frequency of DC within peripheral blood increased rapidly, followed by a marked accumulation of DC within the lung interstitium and subsequently in the alveolar spaces.…”
mentioning
confidence: 99%
“…14,15,44 Immature DCs capture antigen in the peripheral tissue and migrate to the draining lymph nodes, where they activate T cells, and initiate the type-1 or type-2 immune response depending on the presence of IL-12 32,33 or IL-4, 32 respectively. Controversy surrounds the origin of DCs, subsets, and functional differences between subsets, despite considerable recent focus on DC biology.…”
Section: Discussionmentioning
confidence: 99%